First-in-Human Clinical Application of the Medyria TrackCath System in Endovascular Repair of Complex Aortic Aneurysms (ACCESS Trial): A Prospective Multicenter Single-Arm Clinical Trial. (December 2021) - Floros, Nikolaos; Kölbel, Tilo; Tsilimparis, Nikolaos; Oberhuber, Alexander; Kindl, Daniel; Kalder, Johannes; Kotelis, Drosos; Schmidt, Andrej; Branzan, Daniela; Adolf, Daniela; Schelzig, Hubert; Wagenhäuser, Markus Udo
Purpose: The Medyria TrackCath Catheter (MedTCC) is an innovative, thermal convection–based blood flow velocity (BFV) tracking catheter that may be used during complex aortic endovascular procedures for identification and catheterization of target orifices. The ACCESS Trial analyzes the safety and performance of the MedTCC for targeted vessel catheterization to generally evaluate the feasibility of thermal convection–based BFV. Materials and Methods: We performed a first-in-human, proof-of-concept, prospective single-arm multicenter clinical trial between March 2018 and February 2019 in patients who underwent endovascular aortic procedures at 4 high-volume centers. During these procedures, the MedTCC was advanced over a guidewire through the femoral access. The D-shape was enfolded in the reno-visceral part of the aorta and target orifices were identified and catheterized with a guidewire via the side port of the MedTCC through BFV tracking. BFV measurements were performed at baseline (Baseline-BFV), alignment to the orifice (Orifice-BFV), and following catheterization (Confirmation-BFV) to prove correct identification and catheterization of target orifices. The procedural success rate, the catheterization success rate, procedure-related parameters, and (serious) adverse events ((S)AE) during the follow-up were analyzed. Results: A total of 38 patients were included in the safety group (SG) and 26 in the performance group (PG). The procedural success rate was 89% (PG), the MedTCC catheterization success rate was 98% (PG). The MedTCC reliably measured BFV changes indicated by significant differences in BFV between Baseline-BFV and Orifice-BFV (p<0.05). Median (interquartile range; IQR) fluoroscopy time per orifice was 5.0 (1.5–8.5) minutes [total surgery 49 (26–74) minutes], median (IQR) contrast agent used per orifice was 1.0 (0–5.0) mL [total surgery 80 (40–100) mL], and median (IQR) MedTCC-based procedural time was 3.0 (2.0–6.0) minutes. There was no device-related SAE. Conclusions: The ACCESS Trial suggests that BFV measurement allows for reliable target orifice identification and catheterization. The use of MedTCC is safe and generates short fluoroscopy time and low contrast agent use, which in turn might facilitate complex endovascular procedures.